Addition to the List of Brackish Water Zygnemaceae of Sundarbans and its Adjoining Areas, India Genus Spirogyra Link - Naskar, N.M.; Naskar, K.R.; Talai, S. (Our Nature, 2010)
A total 12 species of Spirogyra Link was recorded from brackish water of Indian Sundarbans and its adjoining areas. Spirogyra dubia and Spirogyra ternata are found in the present study which was reported earlier. Spirogyra setiformis is uncommon to the present study which was also recorded earlier. This study represents 10 species of Spirogyra are being reported for the first time from this region. Key words: Algae, brackish water, Spirogyra, Sundarbans, India DOI: 10.3126/on.v7i1.2570 Our Nature (2009) 7:187-192